The audit of fixed assets: verification and the liability of the auditors / Haliza Ibrahim - Ibrahim, Haliza (1986)
"The Audit of Fixed Assets - Verification and the liability of the Auditors", the topic of this project paper will be looked into based on the findings from the method which the writer will mention in the Methodology. The writer will first start the project paper by stating the reason for choosing the topic and what she intends to do with it. The writer will then elaborate the meaning of audit and also the meaning of fixed assets.